Proses Perbaikan Motor Induksi 3300 V 650 KW dengan Rewinding dan Restacking - NUGRAHA, Adhi Prasetya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An induction motor is an alternating current electric motors which the most widely used. Called induction motor as the motor works by the induction of the magnetic field of the stator to the rotor, which the currents of rotor produced by induction that arise cause there is difference of relative between the field rotary rotation rotor (rotating magnetic field) produced by the currents of stator. In the industry, the induction motor is applicated as one of the drivers who used directly to support the production or electricity generation, so that it takes maximum care to maintain the efficiency of the induction motor. One of the factors that can affect the efficiency of an induction motor is winding or winding insulation damage to the motor. In this opportunity for the internship that the writer is working Final Project case study of a 3 phase induction motor squirrel cage rotor with a power output of 650 KW, voltage of 3300 V and a frequency of 50 Hz, where ever there is damage on to the stator. The repaire steps of induction motor are done by restacking process and rewinding process. This process included restacking of core iron, loss test and must be changed with full winding due to the winding has burned it. In the process of reparation thera are many measurements by using a Electrical Apparatus Service Assocation (EASA).